Responsibility for theOrganization of Illegal Migration under the Criminal Legislation ofForeign Countries - Arakelyan, Sergey; Harutyunyan, Narek (Bulletin of Yerevan University C: Jurisprudence, 2024)
The article discusses issues related to the peculiarities of legal norms provided for in the criminal legislation of foreign countries, which establish responsibility for organization of illegal migration. In this regard, an analysis of the relevant legislative acts of the member states of the Eurasian Economic Union, the European Union, as well as a number of other foreign countries (USA, People’s Republic of China, UK, Canada, Australia, Islamic Republic of Iran) is carried out. In particular, it is emphasized that, unlike the countries of the Eurasian Economic Union, in most of the mentioned foreign countries, responsibility for the discussed crime is established not only by the Criminal Code, but also by other legal acts regulating certain spheres. The authors also pays special attention to the fact that the Law on Islamic Punishments of the Islamic Republic of Iran, neighboring Armenia, does not provide for legal norms establishing liability for organization of illegal migration. In this regard, it is emphasized that this country is one of those states in which the organization of illegal migration is not considered as a socially dangerous, criminal phenomenon.